Modeling branching in cereals - Evers, Jochem B.; Vos, Jan (Frontiers in Plant Science, 2013)
Cereals and grasses adapt their structural development to environmental conditions and the resources available. The primary adaptive response is a variable degree of branching, called tillering in cereals. Especially for heterogeneous plant configurations the degree of tillering varies per plant. Functional-structural plant modelling (FSPM) is a modelling approach allowing simulation of the architectural development of individual plants, culminating in the emergent behaviour at the canopy level. This paper introduces the principles of modelling tillering in FSPM, using (I) a probability approach, forcing the dynamics of tillering to correspond to measured probabilities. Such models are particularly suitable to evaluate the effect structural variables on system performance. (II) ‘Dose response curves’, representing a measured or assumed response of tillering to an environmental cue. (III) Mechanistic approaches to tillering including control by carbohydrates, hormones and nutrients. Tiller senescence is equally important for the structural development of cereals as tiller appearance. Little study has been made of tiller senescence, though similar concepts seem to apply as for tiller appearance.